Grammatical genre, textual genre and gender in linguistic studies - doi: 10.4025/actascilangcult.v32i2.9950 - Barros, Dulce Elena Coelho (2010)
Owing to the polysemic nature of the Portuguese term “gênero” and since studies on the grammatical and textual genres deal with the study of issues on gender, current analysis synthesizes in a single text the different forms by which the “grammatical genre” and “textual genre” subjects are de alt with in linguistic studies. The investigation also deals with the interference in these studies of a perspective of gender which agrees with the language’s social characteristics